Analyzing Local Tax Revenue Optimization Strategies Using The SOAR Approach: A Case Study In Susu City - Antoro, Aji Fajar Suryo; Thaha, Abdurrahman Rahim (Educoretax, 2024)
This study uses the SOAR (Strengths, Opportunities, Aspirations, Results) approach to analyze the factors that influence local tax revenue in Boyolali Regency, Central Java. Although regional autonomy provides opportunities, dependence on central transfers is still high. The last five years of data show good target achievement, but the contribution of local own-source revenue (PAD) to the total revenue of the Regional Budget (APBD) is relatively small. Qualitative methods with a post-positivism paradigm were used, and triangulation was carried out based on the results of interviews, observations, and documentation. The results of the study found that Boyolali Regency has not fully met the criteria or standards in the formulation of strategies to increase tax revenue according to the SOAR framework. The strengths of Boyolali Regency lie in the size of its government area, which is the basis of the PBB object, as well as the diversity of local culture. Opportunities are the large number of PBB objects that are still not registered as tax objects and the large amount of uncollected tax receivables. Aspirations are not taken seriously, and the measurement of results has not fully considered the real potential of local tax revenue. In facing this challenge, further efforts are needed to formulate a more comprehensive strategy involving various parties. Suggestions for BKD Boyolali are to consider the utilization of local culture, expansion of the PBB base, increased cooperation that provides added value, increased community participation, and setting targets in accordance with existing regional potential. And the suggestion to the next researcher is to do a comparison with other objects or methods. With the implementation of the right strategy, it is expected to reduce dependence on the transfer of funds from the central government and achieve an increase in local tax revenue and a positive contribution to regional development.